Comparison of the Methods of Surgical Treatment of Complex Congenital Heart Defects Combined with Right Ventricular Hypoplasia - Dziuryi, Ivan V.; Truba, Iaroslav P.; Fylypchuk, Vasyl V.; Perepeka, Iryna A.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Surgical treatment of complex congenital heart defects (CHD) in patients who cannot undergo radical correction due to pronounced hypoplasia or dysfunction of the right ventricle (RV) remains one of the most urgent problems in pediatric cardiac surgery. In 1989, Billingsley et al. first reported the addition of bidirectional cavopulmonary anastomosis to definitive biventricular repair in patients with RV hypoplasia, pulmonary artery atresia, and intact interventricular septum in four patients, and introduced the term one and half ventricle repair (1.5VR). The method of 1.5VR consists of bidirectional cavopulmonary anastomosis, which reduces the volume load on the RV, in addition to the complete repair of other CHDs. The aim. To assess perioperative characteristics of patients, immediate and long-term results after surgical correction of complex CHD through the method of 1.5VR. Materials and methods. In the period from 1996 to 2022, surgical correction was performed in 33 patients with complex CHD combined with hypoplasia and/or dysfunction of the RV at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. There were 21 male patients (64%) and 12 female patients (36%). The mean age of the patients at the time of surgery was 57.9 months. Me = 34 [3.5; 312] months. The main method of diagnosis in determining the defect and assessing the immediate and long-term results was echocardiographic examination and probing of the heart cavities, which made it possible to assess the morphology, kinetics of the heart structures, and hemodynamic state. Depending on the selected tactics of surgical treatment, all the patients were divided into two groups: group І (n=21) with patients operated through the method of 1.5VR, and group ІІ (n = 12) including those operated through the single ventricle pathway. Results. In the early postoperative period, there were 3 (9%) deaths in both groups: one (4.7%) death in group I, and 2 (16%) deaths among patients of group II. In all the deceased patients, the cause of death was acute heart failure, which subsequently led to multiple organ failure. In one patient of the group II, in addition to heart failure, acute cerebrovascular accident occurred. In the group I, the average indicator of systemic saturation (92±6.2%) at discharge from the hospital was higher, than that in group II (87±4.7%). Average duration of mechanical ventilation (10±7.3 vs. 15±7.8 hours), total exudation (65±34 vs. 88.8±39.9 hours), total duration of sympathomimetic support (71±27.5 vs. 108±75.5 hours) and its doses (4.8±2 vs. 6.5±3.8 μkg/kg/hour) were significantly lower in the group I, therefore, the patients of the group II stayed almost twice as long in the intensive care department (146±56 vs. 96±49.8 hours), although the total length of hospital stay did not differ significantly (25±3.8 vs. 26±12.3 days). An uncomplicated course of the early postoperative period was observed in 15 (46%) patients. Other 18 (54%) patients had complications: 8 patients (24%) of group I had 9 complications, and 10 patients (30%) of group II had 14 complications. The mean observation period was 48±29.8 months, (6 to 190 months). No deaths were observed during the observation period in 26 patients (79%) of both groups, 4 (12%) patients were lost to follow-up. Total cavоpulmonary anastomosis (Fontan procedure) was performed in 7 patients (58%) of the group II. Hemodynamic indicators in the examined 17 patients (81%) of the group I showed good long-term results that did not require other interventions. In 15% (3 of 20) of the patients of the group I, a high mean pressure in the right atrium of 14±1.8 mmHg attracts attention with dilatation of the inferior vena cava and hepatic veins, and 5 (20%) patients had high mean pressure of 16±2.7 mmHg in the superior vena cava. Transplantation-free survival during the observation period in patients of both groups was 100%. Conclusions. 1.5VR is a reasonable alternative to the palliative Fontan strategy in children in whom the anatomic or functional status of the RV is between biventricular reconstruction and the single ventricle pathway and shows good immediate and long-term results.